Essays on the Economics of Renewable Energy and Cross-Sectoral Decarbonization. Essays zur Ökonomie erneuerbarer Energien und sektorenübergreifender Dekarbonisierung. - Peter, Jakob (My University, 2019)
This thesis analyzes several aspects of the economics of decarbonizing the electricity and transport sectors. All chapters focus on systems with high shares of variable renewable energies, characterized by time-varying and interdependent temporal and spatial distributions of electricity supply and electricity demand. Chapters 2 and 3 focus on the implications of variable renewable energies on security of supply and how reliability targets can efficiently be reached considering the firm capacity provision of variable renewable energies and interconnectors. Chapter 2 develops, based upon probabilistic reliability metrics, an optimization model to determine the efficient amount and location of firm generation capacity to achieve reliability targets in multi-regional electricity systems. Chapter 3 develops an iteration framework, which allows to combine the previously presented optimization model with a large-scale investment and dispatch model for electricity markets. The framework allows to account for balancing effects in electricity generation and firm capacity provision due to the spatial distribution of generation capacities and interconnectors. Chapter 4 investigates the impact of strong climate change on electricity systems. For Europe, most important are effects on variable renewable energy resources, hydro power availability, cooling water availability for thermal power plants and electricity consumption. Two investment planning strategies are compared in their ability to cope with climate change effects, which are then disentangled in terms of their marginal contribution to the potential welfare loss. Chapter 5 assesses, how the electricity and road transport sector can optimally be decarbonized, accounting for synergies in supply and demand when coupling the two sectors via electrification and power-to-x processes. Thereby, an integrated multi-sectoral partial-equilibrium investment model for the electricity and road transport sectors is developed.
Keywords: Energie; Energiepolitik; Energiewirtschaft; Wohlfahrtsökonomie; Allokation; Erneuerbare Energie; Standort; Region; Energieerzeugung; Dekarbonisierung; Versorgungssicherheit; Strom; Stromversorgung; Strombedarf; Verkehrssektor; Elektroantrieb; Elektrifizierung; Sektorkopplung